Toward a future beyond employment - Cangul, Mehmet; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Toward a Future Beyond Employment proposes that as poor nations move to the emerging stage and as emerging economies become advanced, advanced economies are transitioning to a stage of their own, to a type of post-employment economy where society works less, consumes less, but instead has more time.
Keywords: Unemployment; Leisure